Subacute stroke physical rehabilitation evidence in activities of daily living outcomes: A systematic review of meta-analyses of randomized controlled trials. Issue 8 (February 2019) - García-Rudolph, Alejandro; Sánchez-Pinsach, David; Salleras, Eloy Opisso; Tormos, Josep María
Abstract: Background: Stroke is a leading cause of disabilities worldwide. One of the key disciplines in stroke rehabilitation is physical therapy which is primarily aimed at restoring and maintaining activities of daily living (ADL). Several meta-analyses have found different interventions improving functional capacity and reducing disability. Objectives: To systematically evaluate existing evidence, from published systematic reviews of meta-analyses, of subacute physical rehabilitation interventions in (ADLs) for stroke patients. Methods: Umbrella review on meta-analyses of RCTs ADLs in MEDLINE, Web of Science, Scopus, Cochrane, and Google Scholar up to April 2018. Two reviewers independently applied inclusion criteria to select potential systematic reviews of meta-analyses of randomized controlled trials (RCTs) of physical rehabilitation interventions (during subacute phase) reporting results in ADLs. Two reviewers independently extracted name of the 1st author, year of publication, physical intervention, outcome(s), total number of participants, and number of studies from each eligible meta-analysis. The number of subjects (intervention and control), ADL outcome, and effect sizes were extracted from each study. Results: Fifty-five meta-analyses on 21 subacute rehabilitation interventions presented in 30 different publications involving a total of 314 RCTs for 13, 787 subjects were identified. Standardized mean differences (SMDs), 95% confidence intervals (fixed and random effects models), 95% prediction intervals, and statistical heterogeneity ( I 2 and Q test) were calculated. Virtual reality, constraint-induced movement, augmented exercises therapy, and transcranial direct current stimulation interventions resulted statistically significant ( P < .05) with moderate improvements (0.5 ⩽ SMD ⩽ 0.8) and no heterogeneity ( I 2 = 0%). Moxibustion, Tai Chi, and acupuncture presented best improvements (SMD > 0.8) but with considerable heterogeneity (I2 > 75%). Only acupuncture reached "suggestive" level of evidence. Conclusion: Despite the range of interventions available for stroke rehabilitation in subacute phase, there is lack of high-quality evidence in meta-analyses, highlighting the need of further research reporting ADL outcomes. Abstract : Supplemental Digital Content is available in the text